2012
DOI: 10.5455/aim.2012.20.131-132
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Optic Neuropathy - to Treat or to Observe?

Abstract: We present a case of acute traumatic optic neuropathy in 54 year old male patient. The patient presented with acute loss of vision in the right eye due to a blunt trauma to the eye. Lid haematoma and subconjunctival hemorrhage were present. Fluorescein staining was negative, anterior chamber and lens was clear. Intraocular pressure was normal. Retina and optic nerve head appeared normal on fundoscopy. The vision was “counting fingers at 1 meter” in the right eye. Color test indicated color perception dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Currently, the best treatment for TON patients remains controversial [8,9,10,11,12,13]. Although meta-analysis has shown that both administrations of high-dose steroid and/or surgical decompression contributed to the prognosis of TON, a spontaneous visual recovery rate of 20-38% has also been reported for indirect TON cases [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the best treatment for TON patients remains controversial [8,9,10,11,12,13]. Although meta-analysis has shown that both administrations of high-dose steroid and/or surgical decompression contributed to the prognosis of TON, a spontaneous visual recovery rate of 20-38% has also been reported for indirect TON cases [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Although meta-analysis has shown that both administrations of high-dose steroid and/or surgical decompression contributed to the prognosis of TON, a spontaneous visual recovery rate of 20-38% has also been reported for indirect TON cases [8,9,10]. Moreover, whether nerve sheath incision should be performed during endoscopic optic nerve decompression is still under debate [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who had only soft tissue injuries of the facial region were also not included in this study. (Table 1 and Graph 1): This study revealed that RTA was the major cause of injury and accounts for 77% (156) followed by fall 12.9% (26), and assault 6.9% (14); other causes like sports injury or industrial accidents were only 2.4% (5). Among RTA cases, MTWs were the major (76%, 120) cause of injury.…”
Section: Introductionmentioning
confidence: 79%
“…13 In our study, 5.4% (11) of patients had optic neuropathy, out of which 2.4% (5) had reduced visual acuity at the end of 3 months follow-up. Samardzic et al 14 followed protocol suggested by Cerovski and reported 57.5% of patients on treatment with steroids showed visual improvement in their study. For optic neuropathy, Cerovski suggested that treatment should start preferably within the first 8 hours with megadoses of steroids for otherwise healthy individuals, because all patients were usually scared and psychologically traumatized and expect some sort of treatment when the vision loss is severe.…”
Section: Discussionmentioning
confidence: 96%
“…Traumatic optic neuropathy, which can occur after blast or blunt trauma, 6,13,14 is induced by 2 different injury mechanisms: primary (shearing of the axons and ischemia) and secondary (initial damage and death of the retinal ganglion cells). 15 Given that the majority of Bar graphs of cytokines altered or trending toward an increase after injury. Since changes at 3 and 7 days posttrauma were comparable for most cytokines we also show all sham and all trauma groups combined.…”
Section: Discussionmentioning
confidence: 99%